Apoptosis in myocardial ischaemia and infarction. Issue 11 (1st November 2002) - Krijnen, P A J; Nijmeijer, R; Meijer, C J L M; Visser, C A; Hack, C E; Niessen, H W M
Abstract : Recent studies indicate that, in addition to necrosis, apoptosis also plays a role in the process of tissue damage after myocardial infarction, which has pathological and therapeutic implications. This review article will discuss studies in which the role and mechanisms of apoptosis in myocardial infarction were analysed in vivo and in vitro in humans and in animals.